Assessing and comparing mental skills of men players' positions in volleyball Premier League team of Iran - Chavoshian, M.; Soukhtehzari, S.; Angoorani, H.; Rezaei, M.; Mansour, S. (Sleep and Hypnosis, 2018)
Background and Objectives: Mental skills are important aspects of successful sport performance in all sport competitions. This study was designed to assess and compare the mental skills of men players' positions in premier league volleyball team in year 2015. Materials and Methods: This cross sectional research includes 69 Iran men's premier league volleyball team players in year 2015 who participated in the premier league competitions in year 2015. Mental skills as well as demographic data of the players was assessed by OMSAT-3 questioner and a personal data form. One-way ANOVA was employed to analyze the data. Results: The result of analysis indicated that there was no significant differences between the main components of fundamental (p=0.21), psychosomatic (p=0.12), and cognitive skills (p=0.584) of different positions of the volleyball players. However, there was a significant difference between the sub skills of reaction to stress (0.002) and fear control (0.020) of different positions of volleyball players. Outside hitters and opposite hitter were significantly weaker than the setters, libero and middle blocker in fear control (p<0.05) and reaction to stress (p<0.05). Conclusion: given the importance of mental skills in the achievement of volleyball players, focusing on improving the mental skills of the mentioned positions in volleyball especially in outside hitters and opposite hitter is highly recommended.